La formazione al rispetto dei diritti umani nel sistema penale - Federighi, Paolo; Torlone, Francesca (Studies on Adult Learning and Education, 2013)
The fundamental principles of freedom, security, democracy, and the regulatory mechanisms of the European Union, as well as the pronouncements of the European Convention for the protection of Human Rights and fundamental freedoms (ECHR) can be subject to dangerous violations within criminal justice systems. When these violations are perpetrated by the actors called to protect the same rights and freedoms, the institutions must also prepare the educational devices which are required for their prevention. This volume intends to investigate the complexity of educational actions - primarily informal ones - which accompany the creation of the operators' knowledge of the analysed systems, as well as the methods of their growth. The contents are discussed starting from the research hypotheses, and on the basis of the experimentation of the embedded learning in the prison of Chieti (under the supervision of the Department of Education and Psychology of the University of Florence).